Dangerous bifurcations in 2-dof vibroimpact system - BAZHENOV, V. A.; Pogorelova, O. S.; Postnikova, T. G. (Вісник Національного технічного університету «ХПІ». Серія: Динамiка та мiцнiсть машин, 2016)
Dynamic behaviour of strongly nonlinear non-smooth discontinuous vibroimpact system is studied. Under variation of system parameters we find the discontinuous bifurcations that are the dangerous ones. It is phenomenon unique to non-smooth systems with discontinuous right-hand side. We investigate the 2-DOF vibroimpact system by numerical parameter continuation method in conjunction with shooting and Newton-Raphson methods. We simulate the impact by nonlinear contact interactive force according to Hertz’s contact law. We find the discontinuous bifurcations by Floquet multipliers values. At such points set-valued Floquet multipliers cross the unit circle by jump that is their moduli becoming more than unit by jump. We also learn the bifurcation picture change when the impact between system bodies became the soft one due the change of system parameters. This paper is the continuation of the previous works.